EFFECTIVENESS OF KINESIO TAPING IN IMPROVING MUSCLE STRENGTH AND REDUCING PAIN IN ATHLETES WITH PATELLAR TENDINITIS - AASHNA JAIN; Dr. MONIKA SHARMA (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Patellar tendinitis, a common overuse injury in athletes engaged in repetitive jumping and running sports, leads to anterior knee pain, impaired function, and performance limitations. Conservative management includes exercise therapy, activity modification, and adjunctive modalities such as taping. Kinesio Taping (KT), due to its elastic and skin-mimicking properties, has gained popularity for providing pain relief and functional support without restricting mobility.Aim: To evaluate the effectiveness of Kinesio Taping in improving muscle strength and reducing pain in athletes with patellar tendinitis compared to exercise therapy alone.Methods: Thirty athletes diagnosed with patellar tendinitis were randomly assigned to an experimental group (KT + exercise therapy) and a control group (exercise therapy alone). Pain intensity was assessed using the Visual Analog Scale (VAS), and muscle strength was measured using a handheld dynamometer. Both groups underwent a four-week intervention program, with pre- and post-treatment data collected. Statistical analysis was performed using paired and independent t-tests, with a significance level set at p < 0.05. Both groups demonstrated significant improvements in pain and muscle strength post-intervention (p < 0.05). However, the KT group showed a greater reduction in VAS pain scores (mean difference: –3.4 ± 0.8 vs –2.1 ± 0.7) and a larger increase in quadriceps strength (mean difference: +6.2 ± 1.5 kg vs +3.8 ± 1.2 kg) compared to the control group (p < 0.05).Conclusion: The addition of Kinesio Taping to an exercise-based rehabilitation program resulted in superior pain reduction and greater improvement in quadriceps strength compared to exercise therapy alone in athletes with patellar tendinitis. KT may serve as an effective adjunctive intervention for enhancing short-term functional outcomes in this population.